1996
DOI: 10.1007/bf01718167
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the 3′-terminal region of a Zimbabwe isolate of cowpea aphid-borne mosaic virus (CABMV)

Abstract: The 3'-terminal 1221 nucleotides of a Zimbabwe isolate of cowpea aphid-borne mosaic potyvirus (CABMV) genome have been sequenced. The sequence comprises an open reading frame (ORF) of 990 nucleotides and a 3' non-coding-region of 231 nucleotides followed by a poly-A. The ORF has high similarity to NIb and coat proteins (CP) of potyviruses. A potential CP Q/S cleavage site was identified, yielding a CP of 30.5 kDa containing 275 amino acids. The CABMV sequence is closely related to that of South African passifl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
12
0
4
Order By: Relevance
“…The overall pattern of relationship of the 3 UTR resembles that exhibited by the CP with CrMV being phylogenetically related to different strains of the CABMV cluster ( Figure 2). As observed for the CP, CrMV was shown to be more closely related to CABMV isolates from Brazil [11], Zimbabwe [14] and United States [10] than to the African isolates placed in the other subgroup. Consistent with a previous report [16], CABMV-70.12 was placed outside either subgroup.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The overall pattern of relationship of the 3 UTR resembles that exhibited by the CP with CrMV being phylogenetically related to different strains of the CABMV cluster ( Figure 2). As observed for the CP, CrMV was shown to be more closely related to CABMV isolates from Brazil [11], Zimbabwe [14] and United States [10] than to the African isolates placed in the other subgroup. Consistent with a previous report [16], CABMV-70.12 was placed outside either subgroup.…”
mentioning
confidence: 60%
“…In agreement with Van Boxtel et al [16], BCMNV-NL3 was placed in an intermediate position between the two observed branches. The CABMV cluster diverged into two distinct subgroups, with the Crotalaria-infecting virus consistently placed within the subgroup that included CABMV-Br [11], CABMV-Ga [10] and CABMV-Zi [14]. The overall pattern of relationship of the 3 UTR resembles that exhibited by the CP with CrMV being phylogenetically related to different strains of the CABMV cluster ( Figure 2).…”
mentioning
confidence: 76%
“…1997; Wylie and Jones 2011), CABMV (McKern et al. 1994; Sithole‐Niang et al. 1996; Nascimento et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, Agrobacterium-mediated transformation was used as a tool to evaluate mechanisms of resistance to Cowpea aphid-borne mosaic virus (CABMV) in Nicotiana benthamiana, an experimental host of the virus. CABMV is a positive sense RNA virus that is a member of the genus Potyvirus (Sithole-Niang et al, 1996;Mundembe et al, 2009). In an experiment to evaluate the mechanisms of pathogen-derived resistance, N. benthamiana was transformed with recombinant pBI 121 carrying various forms of the CABMV coat protein gene, following the method of co-cultivation of leaf explants with A. tumefaciens described by An et al (1987).…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 99%